Doğalgaz Sayaçları Akıllı Kalibrasyon Sistemi - Gül, Samet; Özarpa, Cevat (T.C. Bilim, Sanayi ve Teknoloji Bakanlığı, 2014)
As per the Law No. 3516 of Republic of Turkey Ministry of Industry; electric, water and gas meters are required to be periodically inspected and tested every 10 years. Being the largest gas distribution company in Turkey and having 4 millions gas meters, IGDAS (Istanbul Gas Distribution Company), under the said law, has performed calibration Works. Thus, it both fulfilled its legal obligation and sorted out some gas meters with poor measuring precision in its installations and gas losses were also minimized. This paper mainly discusses smart calibration system of natural gas meters.
Smart Calibration Sytem of Natural Gas Meters